The Impact of Scalability and Consistency Management on Database Management System Performance in Big Data Environment in Indonesia - Mardiani, Eri; Sriyeni, Yesi; Sitorus, Astrid Napita; Muthmainah, Hanifah Nurul (The Eastasouth Journal of Information System and Computer Science, 2023)
The swift expansion of technology start-up enterprises in Indonesia demands a deep comprehension of the variables impacting the functionality of Big Data Environments (BDE) and Database Management Systems (DMS). In the context of Indonesian start-ups, this study examines the effects of scalability and consistency management on DMS and BDE. Data from 134 participants were examined using Structural Equation Modeling (SEM-PLS) in a quantitative manner. The findings showed a strong favorable correlation between DMS -> BDE, Scalability -> DMS, and Consistency Management -> DMS. Strong reliability was exhibited by the measurement model, and discriminant validity was verified. While the model fit indices revealed places for improvement, the R Square values indicated an effective explanation of variation. An overview of Indonesian start-up characteristics that is representative was given by the demographic sample study. This research adds knowledge for improving big data and database operations in the dynamic startup environment.